2005
DOI: 10.1590/s0100-879x2005001000006
|View full text |Cite
|
Sign up to set email alerts
|

A connection between extracellular matrix and hormonal signals during the development of the human fetal adrenal gland

Abstract: The human adrenal cortex, involved in adaptive responses to stress, body homeostasis and secondary sexual characters, emerges from a tightly regulated development of a zone-specific secretion pattern during fetal life. Its development during fetal life is critical for the well being of pregnancy, the initiation of delivery, and even for an adequate adaptation to extra-uterine life. As early as from the sixth week of pregnancy, the fetal adrenal gland is characterized by a highly proliferative zone at the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The sensitivity analyses testing potential timing effects suggest that although the effects of maternal subjective distress on the vulnerability of the HPA and HPG axes and at least one behavioral consequence span the entire prenatal period, the second and third trimesters may be particularly vulnerable periods. The second trimester may be a particularly vulnerable period for PNMS to disrupt the relationship between basal testosterone and cortisol response (since the model is weakened without the second trimester exposed), being the time in adrenal gland development when the production of cortisol begins (Chamoux, Otis, & Gallo-Payet, 2005). In contrast, the behavioral consequences in relation to these hormones may be particularly vulnerable to third-trimester exposure, potentially due to changes in neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity analyses testing potential timing effects suggest that although the effects of maternal subjective distress on the vulnerability of the HPA and HPG axes and at least one behavioral consequence span the entire prenatal period, the second and third trimesters may be particularly vulnerable periods. The second trimester may be a particularly vulnerable period for PNMS to disrupt the relationship between basal testosterone and cortisol response (since the model is weakened without the second trimester exposed), being the time in adrenal gland development when the production of cortisol begins (Chamoux, Otis, & Gallo-Payet, 2005). In contrast, the behavioral consequences in relation to these hormones may be particularly vulnerable to third-trimester exposure, potentially due to changes in neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a putative role for ECM expression has been hypothesized in the development of human adrenal cortex (41). Moreover, a previous transcriptome study on ACAs identified enrichment in genes related to ECM (42).…”
Section: Discussionmentioning
confidence: 99%
“…Also it was established that when human fetal adrenal cells were cultured on collagen-coated dishes, laminin and fibronectin, Collagen IV and laminin enhanced proliferation whereas fibronectin increased cell death (34) . Moreover, another study suggested that centripedal migration of the cells of the adrenal is driven by the extracellular matrix components including collagen, and that the extracellular matrix and the signaling hormones as Angiotensin II and ACTH are noteworthy interconnected and share common pathways involved in adrenal gland activity regulation (35).…”
Section: Discussionmentioning
confidence: 99%